ปัจจัยที่มีผลต่อปริมาณการนำเข้าเหล็กลวดของประเทศไทยจากสาธารณรัฐประชาชนจีน: Factors Affecting Import Demand for Wire Rod of Thailand from People’s Republic of China - เกศกาญจน์, เกศกาญจน์; พงษ์พิษณุพิจิตร์, จีรศักดิ์; พัฒนรังสรรค์, พัฒน์ (Journal of Applied Economics and Management Strategy, 2018)
การศึกษาครั้งนี้มีวัตถุประสงค์ เพื่อ 1) วิเคราะห์ปริมาณการนำเข้าเหล็กลวดจากประเทศจีน ปริมาณการผลิตเหล็กลวดภายในประเทศ และตลาดผู้ใช้งานเหล็กลวดของไทย 2) เพื่อศึกษาปัจจัยที่มีผลต่อปริมาณการนำเข้าเหล็กลวดไม่เจืออัลลอยด์และเจืออัลลอยด์จากประเทศจีนและปัจจัยที่มีผลต่อความต้องการของอุตสาหกรรมก่อสร้างและรถยนต์ซึ่งเป็นผู้ใช้งานเหล็กลวด โดยแบ่งการวิเคราะห์ข้อมูลเป็นสองส่วนคือ การบรรยายสภาพทั่วไปของอุตสาหกรรมเหล็กและเหล็กลวด รวมถึงอุตสาหกรรมต่อเนื่อง และการหาความสัมพันธ์ของตัวแปรอิสระต่อตัวแปรตาม โดยใช้ข้อมูลทุติยภูมิรายไตรมาส ตั้งแต่ 1/2547 ถึง 4/2557 รวม 44 ไตรมาสประมาณการด้วยวิธีกำลังสองน้อยที่สุดสองชั้น ผลการวิจัยพบว่า เหล็กลวดมีการผลิตลดลงและมีการนำเข้าสูงขึ้นโดยเฉพาะเหล็กลวดเจืออัลลอยด์จากประเทศจีน จากการประมาณการ 4 แบบจำลองได้ดังนี้ 1) ปัจจัยที่มีผลต่อปริมาณนำเข้าเหล็กลวดไม่เจืออัลลอยด์อย่างมีนัยสำคัญทางสถิติ ณ ระดับนัยสำคัญ 0.01 คือ มาตรการปกป้องการนำเข้า ณ ระดับนัยสำคัญ 0.10 คือ ราคานำเข้าโดยเปรียบเทียบระหว่างเหล็กลวดไม่เจืออัลลอยด์และเจืออัลลอยด์ และ ผลิตภัณฑ์มวลรวมภายในประเทศด้านการก่อสร้าง 2) ปัจจัยที่มีผลต่อผลิตภัณฑ์มวลรวมภายในประเทศด้านการก่อสร้างอย่างมีนัยสำคัญทางสถิติ ณ ระดับนัยสำคัญ 0.01คือ การขอจดทะเบียนอาคารชุด และ ณ ระดับนัยสำคัญ 0.10 คือ ดัชนีราคาบ้านและที่ดิน 3) ปัจจัยที่มีผลต่อปริมาณการนำเข้าเหล็กลวดเจืออัลลอยด์อย่างมีนัยสำคัญทางสถิติ ณ ระดับนัยสำคัญ 0.01 คือ ราคานำเข้าโดยเปรียบเทียบระหว่างเหล็กลวดเจืออัลลอยด์จากประเทศจีนและญี่ปุ่น ณ ระดับนัยสำคัญ 0.05 คือ อัตราแลกเปลี่ยนและปริมาณความต้องการรถยนต์ 4) ปัจจัยที่มีผลต่อความต้องการรถยนต์อย่างมีนัยสำคัญ ณ ระดับนัยสำคัญ 0.01คือ ผลิตภัณฑ์มวลรวมภายในประเทศไทย และ ณ ระดับนัยสำคัญ 0.05 คือ ดัชนีความเชื่อมั่นผู้บริโภค การวิจัยพบว่าหากต้องการใช้นโยบายปกป้องการนำเข้ารัฐบาลควรศึกษาถึงผลกระทบของอุตสาหกรรมเหล็กและอุตสาหกรรมต่อเนื่องโดยใช้หลักการชดเชย เพื่อให้เกิดประโยชน์ต่อสองอุตสาหกรรม รวมถึงเน้นการวิจัยและพัฒนาเพื่อผลิตเหล็กคุณภาพดีและต้นทุนต่ำ This study were to 1) analyze wire rod imported from China, wire rod produced domestically, and markets that use domestic wire rod and wire rod import from China, wire rod domestic production and demand markets of wire rods in Thailand 2) investigate factors affecting import demand of two types of wire rod, alloy and non-alloy types, from People’s Republic of China and determine factors for demand of wire rods from construction & automotive sectors. The secondary data was collected from journal, electronic pubic data for descriptive & quantitative analyses. Quarterly data from Q1/2004 to Q4/2014 was used to estimate regression model which was analyzed by Two-Stage Least Squares (2SLS). The results of 4 models in this study showed that 1) factors determining import amount of non-alloy wire rod from China are anti-dumping policy with a significance level of 0.01. Meanwhile, the relative import price of non- alloy to alloy wire rod and the GDP of construction sector were statically significant at the level of 0.10 2) factors determining GDP 0f construction is new condominium registration which showed a significance level of 0.01, while price index of home and land showed statistically significant level of 0.10 3) factors affecting import amount of alloy-wire rod at a significance level of 0.01 are relative import price of wire rod from China to that of from Japan. Meanwhile, the variables of exchange rate and demand for car showed a significance level of 0.05 4) factors determining demand for cars are Thailand’s GPD which showed a significance level of 0.01 and customer confident index which showed a significance level of 0.05. The study found that to use protection policies, the government should study the impacts of wired rod and continuing wire rod industries by considering compensation principle in order to benefit both industries. In addition, the government should focus on R&D (Research and Development) of steel production with desirable quality and low costs.